On singularities of capillary surfaces in the absence of gravity - V. Roytburd (International Journal of Mathematics and Mathematical Sciences)
We study numerical solutions to the equation of capillary surfaces in trapezoidal domains in the absence of gravity when the boundary contact angle declines from 90° to some critical value. We also discuss a result on the behavior of solutions in more general domains that confirms numerical calculations.